2018
DOI: 10.4168/aair.2018.10.4.406
|View full text |Cite|
|
Sign up to set email alerts
|

Tolerogenic Dendritic Cells Reduce Airway Inflammation in a Model of Dust Mite Triggered Allergic Inflammation

Abstract: PurposeThe use of tolerogenic dendritic cells (TolDCs) to control exacerbated immune responses may be a prophylactic and therapeutic option for application in autoimmune and allergic conditions. The objective of this work was to evaluate the effects of TolDC administration in a mouse model of allergic airway inflammation caused by mite extract.MethodsMouse bone marrow-derived TolDCs were induced by incubation with granulocyte-macrophage colony-stimulating factor (GM-CSF) and dexamethasone, and then characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…Monocyte‐derived tDCs of healthy individuals were demonstrated to favor differentiation of allergen‐specific Treg cells and in turn suppress T‐cell responses. In mouse models, tDCs were revealed to inhibit allergic airway inflammation . Better understanding of DCs with tolerogenic properties may contribute to the development of new therapy regimens, not only in allergy and asthma, but also autoimmunity and organ transplantation.…”
Section: An Overview Of Allergen‐specific Immunotherapy Mechanismsmentioning
confidence: 99%
“…Monocyte‐derived tDCs of healthy individuals were demonstrated to favor differentiation of allergen‐specific Treg cells and in turn suppress T‐cell responses. In mouse models, tDCs were revealed to inhibit allergic airway inflammation . Better understanding of DCs with tolerogenic properties may contribute to the development of new therapy regimens, not only in allergy and asthma, but also autoimmunity and organ transplantation.…”
Section: An Overview Of Allergen‐specific Immunotherapy Mechanismsmentioning
confidence: 99%
“…This effect is probably caused by the immunosuppressive profile of tolerogenic dendritic cells, which have low immunostimulatory capacity, but with potential of inducing Treg cells via IL-10 secretion. As shown by recent studies, tolerogenic dendritic cells producing IL-10 induce tolerance via activation of Treg cells in murine models of autoimmune disease (22,34,35). Interestingly, in the absence of DCs, IL-10 is a cytokine which alone can induce FoxP3 expression and Treg differentiation (42).…”
Section: Discussionmentioning
confidence: 96%
“…The protocol used to produce dendritic cells (DCs) was adapted from a previously described methodology (22). Bone marrow from C57BL/6 mice was collected by flushing the femurs with RPMI medium (Sigma-Aldrich).…”
Section: Generation Of Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, DCs may present distinct phenotypic and functional characteristics according to the stimulus that they received. Ample evidence has demonstrated that DCs differentiated under certain conditions are capable of inducing immune tolerance in multiple disease models ranging from autoimmune to allergic diseases [3][4][5][6][7] . These specific tolDCs are distinguished by the decreased expression of costimulatory molecules and proinflammatory cytokines along with enhancement of anti-inflammatory cytokines, thus leading to T cell anergy and Treg activation 8 .…”
mentioning
confidence: 99%